Pembuatan dan Penggunaan Replika Sedimen Tsunami Purba untuk Media Pembelajaran Tsunami - Walid Amri*; Nazli Ismail; Cut Dewi (Universitas Syiah Kuala, 2022)
The evidence of past disasters can be used to support disaster risk reduction efforts. Many records of past disasters are obtained in the field based on geological studies related to disasters, for example the paleotsunami sediments of the Gua Ek Leuntie. The education process for this evidence cannot be carried out directly in the field. Therefore, an effort is needed so that evidence of past disasters can be presented to the community, for example through making replicas. This study aims to describe the process of making a replica of the Gua Ek Leuntie tsunami sediment and evaluate its design and use as a learning tool about the tsunami. Making a replica of the tsunami sediment of the Gua Ek Lentie was carried out using modeling techniques. The replica was placed in the Tsunami Museum to be assessed for its design and use by visitors, museum staff and artists. Data were collected by using observation and semi-structured interview techniques and then analyzed by qualitative descriptive. The result obtained is a replica that is similar to the original. Analysis of the design and use shows that replica can be a learning tool about tsunami